ANALYSIS OF ROAD PERFORMANCE IN THE MAMBO MARKET CULINARY AREA DUE TO SIDE OBSTACLES-MAJALENGKA - Dini Widyanti; Indrastuti; Adinda Fajarika (Fakultas Teknik Sipil dan Perencanaan, 2024)
Roads are an essential means of transportation to connect various places such as industrial centers, agricultural land, and residential areas and to distribute goods and services to support the economy. Rapid economic growth in Indonesia has also increased the number of private vehicles. This dramatically impacts the balance between the number of cars driving and the capacity of a road. The type of research used this time is qualitative research. Qualitative research is research that usually uses analysis and descriptive. The data collected is in the form of primary and secondary data. Preliminary data is obtained by surveying the research location to get an accurate picture of the situation and conditions. Meanwhile, secondary data is data obtained by collaborating with related agencies for data obtained such as Research location and road situation map. The location of this research is on Jalan. Ahmad Yani. The results of the discussion can be concluded that the volume of traffic flow at the intersection of four Mambo markets at peak hours, namely 16.30 - 17.30 WIB, heading north, gets 103 SMP/hour, in the south direction gets 102.25 SMP/hour, in the west gets 124.95 SMP/hour. The east direction gets 117 SMP / hour with a 134.3 SMP/hour side drag factor.